Nocebo response intensity and influencing factors in the randomized clinical trials of irritable bowel syndrome: A systematic review and meta-analysis - Li, Ruijie; Chen, Fuping; He, Xuanxuan; Feng, Yuqing; Pei, Qiaoqiao; Wang, Dongke; Liu, Xinghuang; Liu, Jinsong; Hou, Xiaohua; Bai, Tao (Frontiers in Medicine, 2022)
Objective: To estimate the magnitude of the nocebo response and explore its influencing factors in irritable bowel syndrome. Methods: The PubMed, Embase and Cochrane Library databases were searched up to March 2021. Parallel-designed, randomized, placebo-controlled trials investigating pharmacological interventions in patients with irritable bowel syndrome were included. We performed a random effects meta-analysis of the proportion of adverse events in placebo-treated participants and evaluated the effect of trial characteristics on the magnitude of the nocebo response rate. Results: 6107 studies were identified from the databases. After evaluation, 53 met the eligibility criteria and were included. The overall pooled nocebo response rate was 32% (95% CI:26%-38%). The most commonly reported AEs were headache(9%), nasopharyngitis(7%), abdominal pain(4%), and nausea(4%). The nocebo response rate was low compared with that in the treatment group applying probiotics, antispasmodics and Traditional Chinese medicine, but high compared with that in antibiotic treatment group .The nocebo rate in patients using diaries to record adverse events was lower than the average, and was higher in patients recording through checkup. Discussion: Patients with irritable bowel syndrome have significant nocebo response intensity in clinical trials. Based on findings in this study, we recommend the researchers pay attention to the common adverse events and carefully analyze the relation to the intervention.